Maritime Security Risks, Vulnerabilities and Cooperation Uncertainty in the Indian Ocean - Cordner, Lee (New Security Challenges, 2018)
This book uniquely employs risk and vulnerability approaches to advocate international policy options for enhancing maritime security cooperation in the Indian Ocean region. Understanding shared risks and common vulnerabilities that impact the achievement of mutual objectives in the oceanic domain present practical bases for progressing collective action. The Indian Ocean sea lanes are the world's most important thoroughfares for energy resources (oil, gas and coal) and other cargoes. Secure maritime trade routes are vital to global, regional and national economies. Further, security challenges resulting from marine environmental degradation impacted by climate change are rising. Regional and extra-regional actors need to work more closely together to impose law and order at sea, control regional conflicts, respond to humanitarian crises and natural disasters, and conserve the marine environment. This book provides an invaluable resource for political leaders, policy advisers, academic researchers, military professionals, and students of international security and strategic studies.